Hepatic mitochondrial oxidative phosphorylation is normal in obese patients with and without type 2 diabetes. (1st August 2016) - Lund, Michael Taulo; Kristensen, Marianne; Hansen, Merethe; Tveskov, Louise; Floyd, Andrea Karen; Støckel, Mikael; Vainer, Ben; Poulsen, Steen Seier; Helge, Jørn Wulff; Prats, Clara; Dela, Flemming
Abstract : Key points: Hepatic insulin resistance in patients with obesity or type 2 diabetes has been suggested to result from hepatic mitochondrial dysfunction. High‐resolution respirometry (HRR) can be used to assess oxidative phosphorylation by measuring the mitochondrial oxygen consumption rate in the individual complexes of the mitochondria. By using HRR, the present study demonstrates no difference in hepatic mitochondrial oxidative phosphorylation among subjects with obesity with or without type 2 diabetes and non‐obese controls. Furthermore, the amount of mitochondria, assessed by the citrate synthase activity, is not different between the three groups. Together the present findings indicate that hepatic mitochondrial oxidative phosphorylation capacity is not impaired in patients with obesity or type 2 diabetes. Abstract: Obese patients with type 2 diabetes (T2DM) and without type 2 diabetes (OB) are characterized by high hepatic lipid content and hepatic insulin resistance. This may be linked to impaired hepatic mitochondrial oxidative phosphorylation (OXPHOS) capacity. The aim of the present study was to investigate and compare hepatic mitochondrial OXPHOS capacity in T2DM, OB and non‐obese controls (CON). Seventeen obese patients (nine OB and eight T2DM) and six CON patients had perioperative liver biopsies taken. Samples were divided into three parts to measure (1) complex I, II and IV linked respiration, (2) citrate synthase (CS) activity and (3) lipid droplet (LD) size and area (% of total tissue area filled by LDs). State 3 respiration of complex I, II and IV and the CS activity did not differ in OB, T2DM and CON. LD size was significantly higher in T2DM compared with CON, and LD area tended ( P = 0.10) to be higher in T2DM and OB compared with CON. The present findings indicate that hepatic OXPHOS capacity is not different in patients with markedly different weight and glycaemic control. Furthermore, the results do not support impaired hepatic mitochondrial respiratory capacity playing a major role in the development of obesity‐induced type 2 diabetes. Key points: Hepatic insulin resistance in patients with obesity or type 2 diabetes has been suggested to result from hepatic mitochondrial dysfunction. High‐resolution respirometry (HRR) can be used to assess oxidative phosphorylation by measuring the mitochondrial oxygen consumption rate in the individual complexes of the mitochondria. By using HRR, the present study demonstrates no difference in hepatic mitochondrial oxidative phosphorylation among subjects with obesity with or without type 2 diabetes and non‐obese controls. Furthermore, the amount of mitochondria, assessed by the citrate synthase activity, is not different between the three groups. Together the present findings indicate that hepatic mitochondrial oxidative phosphorylation capacity is not impaired in patients with obesity or type 2 diabetes.